2009
DOI: 10.1002/pds.1786
|View full text |Cite
|
Sign up to set email alerts
|

Increase in lipid‐lowering treatment rates among TRICARE beneficiaries: a population‐based study

Abstract: The MHS experienced a significant increase in LLT among patients at greatest risk for cardiovascular disease. However, treatment may still be underutilized as approximately one-third of high-risk patients did not receive lipid-lowering medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…These trends are consistent with previously reported cholesterol treatment rates in various surveys, which showed that 18% of high-risk patients received lipid-lowering therapy in 1999, with increases to 38% in 2001 and 65% by 2006. 8,[10][11][12][13][14] The findings in this analysis indicate a trend of continued growth in lipid-lowering treatment rates for high-risk patients through 2008. Approximately 26% of the treated patients in this study achieved the optional LDL-C target level of ,70 mg/dL, similar to the 30% rate of attainment reported recently for high-risk patients with CHD or AVD receiving lipidlowering therapy.…”
Section: Discussionmentioning
confidence: 78%
“…These trends are consistent with previously reported cholesterol treatment rates in various surveys, which showed that 18% of high-risk patients received lipid-lowering therapy in 1999, with increases to 38% in 2001 and 65% by 2006. 8,[10][11][12][13][14] The findings in this analysis indicate a trend of continued growth in lipid-lowering treatment rates for high-risk patients through 2008. Approximately 26% of the treated patients in this study achieved the optional LDL-C target level of ,70 mg/dL, similar to the 30% rate of attainment reported recently for high-risk patients with CHD or AVD receiving lipidlowering therapy.…”
Section: Discussionmentioning
confidence: 78%
“…Cross‐sectional population‐based studies, in which statin use was associated with lower CRP levels, have supported these results . Given the increasing prevalence of statin drug usage, population‐wide CRP levels may be decreasing along with decreasing cholesterol levels . When longitudinal changes in CRP were stratified according to statin use, 10‐year decreases were observed in continual and new users of statins but not in nonusers.…”
Section: Discussionmentioning
confidence: 83%
“…[36][37][38] Given the increasing prevalence of statin drug usage, population-wide CRP levels may be decreasing along with decreasing cholesterol levels. 39 When longitudinal changes in CRP were stratified according to statin use, 10-year decreases were observed in continual and new users of statins but not in nonusers. Similar trends were observed for NSAID use in this study, although results from previous studies on the effects of NSAIDs on CRP have been variable.…”
Section: Discussionmentioning
confidence: 98%
“…Cardiovascular hospitalization was defined as a composite of CV events recorded in the hospital discharge claim and recorded in the primary diagnosis field. CV events were identified by ICD diagnosis codes, diagnosis‐related group codes, or Current Procedural Terminology codes, based on previously published CV outcome codes …”
Section: Methodsmentioning
confidence: 99%
“…CV events were identified by ICD diagnosis codes, diagnosis-related group codes, or Current Procedural Terminology codes, based on previously published CV outcome codes. [22][23][24][25][26][27][28][29] All-cause death was defined as death from any cause identified in inpatient hospital settings. Since administrative databases may not reliably capture death, an additional method was used as a proxy to identify death cases.…”
Section: Key Pointsmentioning
confidence: 99%